Kemampuan Theory of Mind Anak Usia 3-5 Tahun Ditinjau dari Intensitas Interaksi dengan Saudara Kandung - Azizah, Nur (Jurnal Psikologi Tabularasa, 2015)
Basically preschool age children should be aware that each individual has thoughts, feelings, desires, and other mental conditions which is different from himself. This awareness is known as theory of mind, and one of the factors that could be expected to stimulate the ability of theory of mind is the intensity of the interaction between children and their siblings. The basic concept of the theory used in this study is the cognitive development of sociocultural perspectives of leading experts Lev Vygotsky. The study was conducted in three schools Kindergarten (TK) in Yogyakarta, with the subject as much as 31 children aged 47-69 months. The measurements used are false belief task, and Scale "intensity of interaction between children and siblings" were made by researchers. Siblings age limit is a maximum of 12 years of age brother and sister at least 1 year of age. Data analysis using binary logistic regression analysis, the results of analysis show that the value of Wald 1.036 (p> 0.05), so it can be concluded that the intensity of the interaction between children and siblings are not able to predict the ability of theory of mind. It is suspected the influence of siblings and their age difference in the way children interact with siblings between Western and Eastern cultures, including cultures in Indonesia